PENGELOLAAN MANAJEMEN GAPOKTAN DALAM MENINGKATKAN PEREKONOMIAN PADA MASA PANDEMI COVID 19 DI DESA TEBAS KUALA KECAMATAN TEBAS - Wahab Wahab; Gustina Gustina; Jum’an Jum’an (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2022)
This community service activity is in the form of training in Gapoktan management which aims to provide knowledge and insight, especially on human resources (farmers), marketing of agricultural products and financial management so that they can improve the performance and productivity of agricultural products for the economic welfare of the people of Tebas Kuala Village. The target in this activity is the management of Gapoktan and farmer groups in Tebas Kuala Village, totaling 15 people. The training was conducted using lecture and question and answer methods. Community Service Activities can be carried out properly and run smoothly in accordance with the activity plans that have been prepared, although not all participants have mastered the material presented well. This activity received a very good response as evidenced by the active participation of participants in the training until it was completed. This Community Service activity is to provide solutions to the Farmers Group Association (Gapoktan) for the problems it faces. The training that has been carried out is able to increase the knowledge of the trainees. Participants showed an attitude of wanting to change work habits that were less disciplined to be active and enthusiastic. In addition, having the will to create superior products in order to create more benefits, get to know online marketing, know the process of preparing financial reports and adjust the types of financial reports made, recording sales and other costs